Formulation And Activity Tests Of Anti Dandruff Shampoo Ethanol Extract Of Peperomia Pellucida (L.) Kunth Leaves On The Growth Of Pityrosporum Ovale Fungus - Abadi, Hafizhatul; Eulis, Vivi (International Archives of Medical Sciences and Public Health, 2023)
Shampoo is a cosmetic preparation used to clean hair. The leaves of Peperomia pellucida (L.) Kunth are one of the plants that can be used to get rid of dandruff. The plants contain alkaloids, saponins, tannins, hydroxylated sesquiterpenes, especially carotol and peppermint which have antifungal activity. Purpose; formulating anti-dandruff shampoo preparations containing suruh leaves, as well as evaluating shampoo preparations which include homogeneity, pH, organoleptic tests, foam height, viscosity, and irritation. Method; The research method used was an experimental method, namely Peperomia pellucida (L.) Kunth leaf extract obtained by maceration method, then formulated as an anti-dandruff shampoo preparation starting with making a base consisting of sodium lauryl sulfate, cocamydopropyl betaine, polyquaternium 7, methyl paraben, sodium chloride, citric acid, menthol, rose perfume, and distilled water. Then added the extract of the leaves of the order each with a concentration of 1%, 3%, and 5%. The results obtained were then tested statistically with one way type ANOVA. Results:. The ethanol extract of suruh leaves can be formulated as an anti-dandruff shampoo preparation, and the ethanol extract of suruh leaf anti-dandruff shampoo preparations with a concentration of 5% has provided an effective inhibition against the growth of the fungus Pityrosporum ovale. Conclusion; The concentration of the ethanol extract of suruh leaves anti-dandruff shampoo which has an effective inhibitory activity against the growth of the fungus Pityrosporum ovale is in formula III with an inhibition zone of 14.2 mm.